1994
DOI: 10.1002/jnr.490370508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nerve segment supernatants on cultured Schwann cell proliferation and laminin production

Abstract: Mouse sciatic nerves were transected and 3 hr to 16 days later proximal segments were removed and homogenized. Supernatants of these segments or of normal sciatic nerves were added to Schwann cells maintained in Dulbecco's modified Eagle's medium (DMEM) + 15% fetal calf serum (FCS). After 6 days, Schwann cells were solubilized and the protein content was measured using a Bio-Rad (Melville, NY) protein assay. Samples containing the same amounts of protein were then applied to microtiter plates and the laminin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…Immunostaining for 5-bromo-2 '-deoxyuridine-5 '-monophosphate (BrdU) -incorporated DNA. Immunodetection of cells containing BrdU (Sigma) incorporated into DNA was performed as described previously (Zhang et al, 1994). P19 cells were pulse treated with 10 ,iM BrdU in sequential overnight (16 h) intervals before, during, and after exposure to RA.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Immunostaining for 5-bromo-2 '-deoxyuridine-5 '-monophosphate (BrdU) -incorporated DNA. Immunodetection of cells containing BrdU (Sigma) incorporated into DNA was performed as described previously (Zhang et al, 1994). P19 cells were pulse treated with 10 ,iM BrdU in sequential overnight (16 h) intervals before, during, and after exposure to RA.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…We used previously described methods for laminin determinations (Winston, 1992;Zhang et al, 1994). Cultured Schwann cells were lysed and centrifuged at 12,500 rpm.…”
Section: Elisa For Lamininmentioning
confidence: 99%
“…Recently, we have been interested in whether neuropeptides regulate some axon‐Schwann cell interactions during the early stages of nerve regeneration. Initially, we found that supernatants prepared from proximal nerve segments 12–48 hours after transection upregulated laminin synthesis in cultured Schwann cells ( Zhang et al, 1994 ) . To test whether a neuropeptide might be responsible for this effect, we exposed cultured Schwann cells to medium containing VIP.…”
Section: Introductionmentioning
confidence: 99%